Jiangtang Tongmai Prescription Reduced Diabetic Lung Injury Through SnoN and TGF-β1/Smads Signaling Pathway - Ding, Nian; Zheng, Chenghong (Frontiers in Endocrinology, 2022)
By establishing a rat diabetes model in rats with intervening treatment by Jiangtang Tongmai Prescription (JTTMP), this study explored the restorative pairing effect of JTTMP on diabetic lung injury. The model of type II diabetes model was used to establish the rat diabetes model, using a high-fat diet and streptozotocin (STZ) induction. Different doses of JTTMP and metformin were administered as a therapeutic to intervene, and blood was collected to assess the blood glucose level of each group of rats. HE (Hematoxylin and eosin (H&E) staining was performed to detect the morphological changes in rat lung tissue and enzyme-linked immunoassay ELISA was used to detect and quantify the expression of interleukin (IL)-6, TNF tumor necrosis factor-ɑa, and IL-1β in serum and the lung tissue of each group of rats. The level expression of TGF-β1 [transforming growth factor (TGF)-β1), SnoN (transcriptional co-repressor Ski-N terminal (SnoN)], Smad2, Smad3, Smad7, and other signaling pathway proteins were assessed by Western blot. In comparison with the normal control (NC) group, rats in the diabetes model (DM) group lost weight and showed significantly increased blood sugar levels. The levels of TGF-β1 and Smad2/3 were increased in the DM group but Smad7 decreased. After 8 weeks of JTTMP intervention, the level of TGF-β1 and Smad2/3 decreased but Smad7 increased, blood sugar decreased significantly and the expression of inflammatory factors in lung tissue decreased. Therefore, JTTMP may activate SnoN and the downstream TGF-β1/Smads signaling pathway to repair diabetic lung injury, which suggests its application has potential for future clinical treatment of diabetes with lung injury.